Microfluidic Biochemical Sensor Based On Circular SIW-DMS Approach For Dielectric Characterization Application - Zakaria, Zahriladha; Mohd Bahar, Amyrul Azuan; Al-Ahnomi, Rammah Ali Hussien; Sam, Weng Yik; Md Arshad, Mohd Khairuddin; Abu-Khadrah, Ahmed Ismail Mohammad (Wiley Periodicals, Inc., 2019)
This work proposes an advancement of microwave planar resonator sensor with high sensitivity for microfluidic dielectric characterization. The physical design was employed based on circular substrate integrated waveguide (CSIW) with an integration of defected microstrip structure (DMS). This approach can be applied to accelerate the dielectric detection, structure miniaturization and material differentiation. The presented sensor operates based on variations in the dielectric properties of solvents in the vicinity of a planar open-ended microstrip resonator device. Further analysis in volume and concentration were performed to validate the reliability of the sensor. Validation and functionality of the sensor were investigated by experimental and results comparison. A mathematical model was developed to determine the dielectric constant and the loss tangent of the microfluidic samples. The average error detection has a lower percentage value of 0.11% by comparison to the commercial and ideal dielectric properties of the aqueous samples. The maximum relative error detection, ±0.37% implied better accuracy compared to the existing resonator sensors with more than 400 of the Q-factor. The proposed CSIW-DMS sensor was found to give higher accuracy and detection response; besides easier to fabricate, and compatible for integration with other electronic components in an RF sensor for variety of applications